Scenario-based optimization design of icebreaking bow for polar navigation. (15th January 2022) - Lu, Yu; Gu, Zhuhao; Liu, Shewen; Chuang, Zhenju; Li, Ziying; Li, Chunzheng
Abstract: Global warming and ice extent reduction in Arctic makes commercial shipping through Arctic waters be promising in the near future. The fuel consumption and emission from ships on the Arctic shipping routes, which mainly depends on the ship resistance, is key factor to determine if it is more cost-effective comparing to traditional shipping route. The shipping route in Arctic water include open water and ice-covered water areas. The polar ships traveling through Arctic water need to have ice-strengthened hull to have ice-breaking capability to proceed safely in ice-covered water. Usually the bow hull form with good ice-breaking capability have high resistance in open water, while the bow form with good open-water efficiency (such as bulbous bow) may not have ice-breaking capability. This paper is to develop a methodology for optimized hull form design so that the minimum overall resistance in open-water and ice-covered water can be achieved, while maintaining desired level of ice-breaking capability for considered shipping route with expected ice conditions. The methodology proposed in this paper is based on the ship's desired route with historic ice data to define its typical operation profile. For the test example of this methodology, based on the desired route, the historic ice data are extracted from public available data source to determine the sections of open-water and ice-covered water, as well as the ice-thickness distribution along the route. The ship's resistance in open-water is calculated based on Rankine source method, while the ice resistance is calculated by Lindqvist formula. The overall resistance is weight-averaged based on the route's sections of open-water and ice-covered water. The ice-breaking capability is measured by the ice loads giving by the IACS Polar UR, which serves as the constraint during the optimization process. The parametric model is established for the optimization process. With an ice-breaking bow base design, the optimized bow hull form is achieved on the specified shipping route with historic ice condition. The result shows that the overall resistance is reduced by 5.42% while maintaining enough ice-breaking capability for the considered sample ship. Discrete Element Method is used to verify the optimized hull form's ice-breaking performance compatible with original hull form. It is shown that the methodology developed in this paper can be generally applied to polar ship hull form design for different shipping route and ice conditions. Highlights: An optimization procedure for ice-breaking bow hull form based on scenario analysis model is proposed. Ice data of the sample shipping route are analyzed to classify open and ice-covered water with specific ice thickness. The full parametric modeling method is used to model the ship to create hull form variations for optimization. Minimizing total resistance considering open and ice-covered water is optimization target with rule ice loads as constraint. Discrete element method is used to simulate ship/ice interaction for both original and optimized hull form.